Prediction of lamination patterns in Heterolithic sedimentary sequence, offshore Sarawak (Malaysia) - Ali, Y. (Springer Nature, 2019)
This paper aimed at predicting spatio-temporal variations and new lamination patterns based on available core samples and core images. For this purpose, a scan line method was applied on core photographs showing heterolithic laminations to generate a signal. Then, the generated signal from the scan line was analyzed and interpreted as time series data that can be used in many applications. Samples were taken from different depths to reflect the temporal or vertical variations, and their signal data were compiled into one continuous time series. A new pattern of sedimentary structures represented by new signal data was identified and was converted back into sedimentary structures. The predicted pattern varies in space and depth, and therefore, represents variations on both spatial and temporal bases. The study is therefore significant as the prediction of different patterns can provide information on the depositional environment, paleogeography, and petrophysical properties. Â© Springer Nature Switzerland AG 2019.